2011
DOI: 10.1021/cg201007m
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Structures and Tautomerism of Carboxylate Salts of Adenine and Pharmaceutically Relevant N6-Substituted Adenine

Abstract: Co-crystal and salt formation of the kinetin analogue N 6 -benzyladenine with the pharmaceutically acceptable co-crystal and salt formers maleic acid, oxalic acid, glutaric acid, succinic acid, benzoic acid and fumaric acid has been studied by solid-state and solvent-drop grinding in combination with X-ray powder diffraction. In all cases salt or co-crystal formation was observed. Single crystals of (bzadeH + )(mal -) (1) and (bzadeH + )2(ox 2-) (2) were obtained by solution crystallization and the X-ray struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…This d-spacing is larger than one molecular length of Fmoc-Glu (1.34 nm) but shorter than two,indicating abilayer structure of Fmoc-Glu with an overlapping Fmoc moiety.Itwas found that the XRD patterns do not change significantly after assembly with the nucleobase.I nc ontrast, we changed the mixing ratio of Fmoc-Glu to Aa nd investigated their gel formation ( Figure S1), nanostructures ( Figure S10), and CD spectra ( Figure S11), and found that only in the ratio of 2:1, Fmoc-Glu and Af ormed the stable hydrogel and uniform helical fibers.B ased on these results,w es peculate that the nucleobase laterally attached on the bilayer surface of Fmoc-Glu (Figure 4b). Thepurine bases interact with two alternate glutamic acids through hydrogen bonding [17] (Figure 4b, inset), and the bulky purine base may cause the torsion of neighboring Fmoc-Glu molecules.T his purine-base-inserted bilayer structure serves as ab asic repeat unit, which forms multiple bilayers,a nd further hierarchically self-assembles into higher level nanohelices.The larger conjugated structure of purine nucleobases than that of pyrimidines is attributed to stronger p-p stacking, causing the formation of hydrogels and chiral structures.After inserting ThT, the d-spacing is aslightly enlarged (2.72 nm), and the increment (0.32 nm) may be ascribed to the length of the dimethylbenzenamine moiety. Thebenzothiazole moiety is inserted into the bilayer to cause the helical pitch to increase further (Figure 4c).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This d-spacing is larger than one molecular length of Fmoc-Glu (1.34 nm) but shorter than two,indicating abilayer structure of Fmoc-Glu with an overlapping Fmoc moiety.Itwas found that the XRD patterns do not change significantly after assembly with the nucleobase.I nc ontrast, we changed the mixing ratio of Fmoc-Glu to Aa nd investigated their gel formation ( Figure S1), nanostructures ( Figure S10), and CD spectra ( Figure S11), and found that only in the ratio of 2:1, Fmoc-Glu and Af ormed the stable hydrogel and uniform helical fibers.B ased on these results,w es peculate that the nucleobase laterally attached on the bilayer surface of Fmoc-Glu (Figure 4b). Thepurine bases interact with two alternate glutamic acids through hydrogen bonding [17] (Figure 4b, inset), and the bulky purine base may cause the torsion of neighboring Fmoc-Glu molecules.T his purine-base-inserted bilayer structure serves as ab asic repeat unit, which forms multiple bilayers,a nd further hierarchically self-assembles into higher level nanohelices.The larger conjugated structure of purine nucleobases than that of pyrimidines is attributed to stronger p-p stacking, causing the formation of hydrogels and chiral structures.After inserting ThT, the d-spacing is aslightly enlarged (2.72 nm), and the increment (0.32 nm) may be ascribed to the length of the dimethylbenzenamine moiety. Thebenzothiazole moiety is inserted into the bilayer to cause the helical pitch to increase further (Figure 4c).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The interest of these systems is aimed at better understanding the intermolecular interactions that are involved in these diverse molecular bio-recognition processes, and to provide tools to aid in the design of efficient tailor-made probes and drugs that could be potentially applied in number of theranostic applications [3,4]. Hydrogen bonding interactions are a major driving force in the formation of numerous supramolecular structures involving nucleobases with a variety of structural geometries [5]. Indeed, natural and artificial host-guest complexes as well as many nucleic acid structural elements are a direct result of specific, highly-directional intermolecular hydrogen bonding interactions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonding interactions are a major driving force in the formation of numerous supramolecular structures involving nucleobases with a variety of structural geometries [5]. Indeed, natural and artificial host-guest complexes as well as many nucleic acid structural elements are a direct result of specific, highly-directional intermolecular hydrogen bonding interactions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, among the dicarboxylates namely maleate anion ( Figure b ) is a key molecule in crystal engineering due to its structural aspects in terms of deprotonation, inter and intramolecular hydrogenbonding functionality and flexible conformational features . Maleate anions were used to complex with different organic components; base molecules, amino acids as well as drug molecules (e. g., quinolone 4‐carbaldoxime, L‐methionine, Adenine, clofazimine, lamivudine, caffine, aminopyridinium, guanidinium, umifenovir, medendazole, tetrathiafulvalene etc.,) and generate polymorphism, salts, solvates, co‐crystals with interesting ring motifs and analyzed their pharmaceutical properties and semiconducting properties . In addition investigations in solution state regarding their solubility or their kinetic stabilities or theoretical studies on proton‐tautamerism 53 and energy parameters are also performed .…”
Section: Introductionmentioning
confidence: 99%